Anatomical and Ultra-sonographic Study of the Aortic Arch Branches in the Native Goat (Capra hircus) - Fatimah Swadi Zghair (Journal of Global Pharma Technology, 2019)
Five health adult goats of Iraqi local breed of both sexes, were collected from Diyala Governorate weighing range between (6-8kg±40.11), and their ages were between (1-3) months. Ultrasound Scanner technique was used to study the aortic arch branches; ultrasonic examinations were done with a real-time B-Mode scanner supplied with a 7.5 MHz-linear array rectal transducer. All these goats were euthanized. The aortic arch of the goats is extended cranially, dorsally, and turn caudally situated below the vertebra columns at the level of the third intercostal space, above the pulmonary trunk. The aortic arch gives two branches in which the short branch called left-subclavian artery and large brachiocephalic trunk. Moreover, the brachiocephalic trunk is a great vessel cranial branch that yields two large branches; right-subclavian artery and bicarotid trunk which divided into left-common carotid artery and right-common carotid artery.Keywords: Anatomy, Aortic arch, Branches, Native goat, Ultrasonography.